Pirfenidone attenuates lung fibrotic fibroblast responses to transforming growth factor-β1 - Jin, Jin (Respir Res, 2019)
BACKGROUND: Pirfenidone, an antifibrotic agent used for the treatment of idiopathic pulmonary fibrosis (IPF), functions by inhibiting myofibroblast differentiation, which is involved in transforming growth factor (TGF)-β1-induced IPF pathogenesis. However, unlike normal lung fibroblasts, the relationship between pirfenidone responses of TGF-β1-induced human fibrotic lung fibroblasts and lung fibrosis has not been elucidated. METHODS: The effects of pirfenidone were evaluated in lung fibroblasts isolated from fibrotic human lung tissues after TGF-β1 exposure. The ability of two new pharmacological targets of pirfenidone, collagen triple helix repeat containing protein 1(CTHRC1) and four-and-a-half LIM domain protein 2 (FHL2), to mediate contraction of collagen gels and migration toward fibronectin were assessed in vitro. RESULTS: Compared to control lung fibroblasts, pirfenidone significantly restored TGF-β1-stimulated fibroblast-mediated collagen gel contraction, migration, and CTHRC1 release in lung fibrotic fibroblasts. Furthermore, pirfenidone attenuated TGF-β1- and CTHRC1-induced fibroblast activity, upregulation of bone morphogenic protein-4(BMP-4)/Gremlin1, and downregulation of α-smooth muscle actin, fibronectin, and FHL2, similar to that observed post-CTHRC1 inhibition. In contrast, FHL2 inhibition suppressed migration and fibronectin expression, but did not downregulate CTHRC1. CONCLUSIONS: Overall, pirfenidone suppressed fibrotic fibroblast-mediated fibrotic processes via inverse regulation of CTHRC1-induced lung fibroblast activity. Thus, CTHRC1 can be used for predicting pirfenidone response and developing new therapeutic targets for lung fibrosis. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12931-019-1093-z) contains supplementary material, which is available to authorized users.